2012
DOI: 10.1007/978-94-007-4716-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Binding Partners

Abstract: GAPDH interacts with a plethora of diverse cellular proteins. The network of interacting partners, or interactome, is presented for GAPDH with the interacting molecules grouped into specific functional and structural categories. By organizing the binding partners in this way, certain common structural features are beginning to surface, such as acidic dipeptide sequences that are found in several of these binding proteins. Additionally, the consensus sequences for target polynucleotides are being brought to lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 99 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…GAPDH interacts with numerous proteins of diverse functions (for a review see ref. 58). To the best our knowledge, this is the first report which describes an interaction between GAPDH and NAOD.…”
Section: Discussionmentioning
confidence: 99%
“…GAPDH interacts with numerous proteins of diverse functions (for a review see ref. 58). To the best our knowledge, this is the first report which describes an interaction between GAPDH and NAOD.…”
Section: Discussionmentioning
confidence: 99%
“…The interactome of GAPDH includes proteins with a role in the membrane transport of proteins, G‐proteins, Ca 2+ ‐binding protein extracellular binding targets, molecular chaperones, and others. The target proteins relevant to our study include misfolded proteins like amyloid β peptide, tau, α‐synuclein and HTT (Seindler ). Recently, we showed that not only is GAPDH present in polyQ aggregates, but it can also augment the latter aggregation (Guzhova et al .…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased recognition of GAPDH's multifunctionality, particularly with regard to neuronal function [2]. We think that in addition to this role (i.e., kinase-dependent phosphorylation of the receptor [1]), GAPDH may also participate in the proper receptor trafficking to the plasma membrane, and perhaps the recycling event.…”
Section: Introductionmentioning
confidence: 99%